Improving anesthesia resident wellness: A facilitated peer discussion group evaluated with a pre-/post-intervention survey - West, Nicholas; Taylor, James D; Luo, Jessica; Newlove, Theresa; Brown, Zoë (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Background: Many residents report a second victim response following near-miss events during their pediatric anesthesia rotation with consequences for their mental and physical wellbeing. This study investigated the impact of a Better Resident Wellness (BREW) initiative at our tertiary pediatric centre.Methods: We invited anesthesia residents to complete a survey at the start of their pediatric rotation. Questions included the Second Victim Experience and Support Tool (SVEST). During their rotation, residents attended weekly BREW rounds, a one-hour peer discussion facilitated by a psychologist. They provided feedback in a follow-up survey, including repeat SVEST.Results: 33/48 (69%) invited residents completed pre- and post-surveys Oct/2021-Feb/2023: all had attended one or more BREW rounds; 32/33 (97%) considered BREW helpful, safe, and would recommend to future residents; perceived benefits included improved morale (30/33, 91%) and clinical care (23/33, 70%). SVEST indicated a second victim response for 17/32 (53%) at the start and 7/32 (22%) at the end of their rotation (odds ratio 0.25, 95% CI 0.07 to 0.82, p = 0.019), with reduced professional self-efficacy concerns (median difference -0.25, 95%CI -0.50 to 0, p = 0.029).Conclusion: BREW offers anesthesia residents a desirable and beneficial support resource. Other residency programs should consider integrating facilitated peer discussion into their curriculum.